2001
DOI: 10.1111/j.1467-839x.2001.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Collectivism coexisting with individualism: an Indian scenario

Abstract: A sample of 292 respondents, drawn from three locations, participated in a study designed to examine the effects of eighteen situations on the choice of collectivist and individualist behaviour and intentions, or their combinations. The findings indicated that concerns for family or family members evoked a purely collectivist behaviour. Compelling and urgent personal needs and goals in conflict with the interests of family or friends led to a mix of individualist and collectivist behaviour and intentions. Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 0 publications
4
116
1
1
Order By: Relevance
“…For instance, an individual may purse individual and personal preferences, such as those associated with dating and marriage, if they also accommodate or at least do not conflict with the needs and interests of family and friends. Few Indians report that they engage in individualistic behaviors with individualistic intentions (Sinha et al 2001(Sinha et al , 2002. Thus, the tendency toward individualism appears to be expressed within a collectivistic framework.…”
Section: The Present Studymentioning
confidence: 89%
See 1 more Smart Citation
“…For instance, an individual may purse individual and personal preferences, such as those associated with dating and marriage, if they also accommodate or at least do not conflict with the needs and interests of family and friends. Few Indians report that they engage in individualistic behaviors with individualistic intentions (Sinha et al 2001(Sinha et al , 2002. Thus, the tendency toward individualism appears to be expressed within a collectivistic framework.…”
Section: The Present Studymentioning
confidence: 89%
“…While all such generalizations have significant limitations, at a societal level, India has recently been investigated as exemplary of a culture with a blend of collectivistic and individualistic behaviors and intentions (Sinha et al 2001(Sinha et al , 2002. Traditional Indian values stress interdependence among family members, hierarchy in social systems, and dharma (or the performance of one's duty), and such collectivistic goals as maintaining social order, social cohesiveness, and interpersonal harmony are the primary concerns and socialization goals (Kapadia and Miller 2005).…”
Section: The Present Studymentioning
confidence: 99%
“…Today, collectivistic meaning systems co-exist with individualistic ones, mainly in urban areas [26]. Additional core values include spirituality [27], meeting social obligations [28], and family-oriented values [29] the role of an authority and a source of wisdom within the family. Today, however, the nuclear family structure is becoming the norm, particularly in urban areas [36].…”
Section: The Indian Context and Older Adultsmentioning
confidence: 99%
“…One's duty towards family is also found to be a defining feature in work-related decisions in India (Gupta & Tracey, 2005). Collectivist societies that display high member interdependence exhibit high individual goal congruence with group goals (Singelis et al, 1995) and it has been found that the 'familial self' is where Indians are most likely to display collectivist tendencies (Sinha, Sinha, Verma, & Sinha, 2001). Family legacy has been described as 'living tradition' or a 'lived understanding' which is constructed and reconstructed over time by family members and generations, and additionally influenced by cultural and societal discourses (Plager, 1999).…”
Section: Literature Overview Callingsmentioning
confidence: 99%